Objektiewe Skrifuitleg? Kanttekeninge by Skrifuitleg in die Ned Geref Kerk 1930-1990 - Deist, Ferdinand (Hervormde teologiese studies, 1991)
Objective interpretation of Scripture? Marginal notes to the interpretation of Scripture in the Dutch Reformed Church 1930-1990 This article seeks to understand developments in biblical scholarship in the Dutch Reformed Church in the period 1930 to 1990 from the perspective of epistemology and methodology, and that of socio-political history. It also tries to explain developments on the epistemological level from the perspective of socio-political history. An explanation is thus attempted for the sometimes confusing fact that apartheid, which was once presented as a ‘biblical’ imperative by the Dutch Reformed Church has recently, on ‘biblical’ grounds, been proclaimed a sin by the same church.